The Factors Associated with The Triage Implementation in Emergency Department - Nur Ainiyah; Ahsan Ahsan; Mukhamad Fathoni (Jurnal Ners, 2015)
Introduction: Triage is defi ned as a process to sort patients based on the severity and emergency situation. In fact, Emergency Department (ED) in several hospitals in Indonesia do not implement it, so not all patients come to Emergency Department due to a true emergency case but there are also a false emergency. Implementing triage is important in order to decrease false emergency case and also increase ED service quality. The research goal was to analyze factors associated with the triage implementation in Emergency Department in Hospitals (type A and B).  Methods: The research design was a cross sectional with corrrelative analysis. The research population was emergency department nurses and patients. Samples were taken by total sampling for the nurses (54 respondents) and accidental sampling for patients (54 respondents). The research instruments were questionnaire and direct observation. The research datas were analized using multivariat logistic regression by backward LR.Results: The result showed that the dominant factors correlated with the implementation of the triage was the performance factor (p value. 0,002), the patient factor (p value = 0.011), and the staffing factor (p value. 0.017).Conclusion: The hospital management can increase the work motivation,then optimize the nurses by giving a job description clearly and improve nursing service quality through Triage Offi cer Course.